Holoxica Limited / Seri Nur Amirah Ramli - Ramli, Seri Nur Amirah (2022)
This study analysed cases that applied hologram technology in our daily life to provide basic information for research on dress up using hologram technology. The results of this study are as follows. A hologram was applied to dress up daily life in various ways including dress up going out with friend, dress up stay at home or dress up when having dinner. Today, as-being the age of smart devices, the hologram technology is growing rapidly among us. The idea came to my mind after contemplating for a while and I considered the idea of Home Holographic Display for Attire Selection which it can scan and display the clothes available inside the closet into an avatar of the user. For this case study, a research on Holoxica Limited is done, where information regarding the company will be explained. The information will be explained regarding on subtopics, which include company background, product, technology, business, and marketing strategy whereas its financial achievement. The first problem it is users tend to difficult to choose to dress up due to their busy schedule. This because uses nowadays are very busy with their burden of works, family fairs, and many things. They are even sloppy dress up because they did not have enough time to take care of themselves and proper dress up. Moreover, users do not want to think so much about dress up because the time a running out so fast. For example, when a woman wants to go the dinner, she is at least taking a 30 minute to think a dress suitable to wear for dinner. Furthermore, users use manual choosing clothes to wear, clothes in the closet become cluttered and unmanageable. From the problem, we get a solution to solve the problem. The solution it is a develop Home Holographic Display for Attire Selection for easier the user to use it. So, from this solution users can use every day and every time if their want to going somewhere or stay at home. This solution can make a good decision for some users have problem to choose the dress up. Lastly, SWOT Analysis is used in this study to determine the company’s strengths, weaknesses, opportunities, and threats. The main objective of the SWOT analysis is to assist organizations or company in developing a full understanding of all the factors involved in the decision-making process.